Functional role of polysaccharide intercellular adhesin during Staphylococcus epidermidis biofilm interaction with the innate immune system. - Rand Jihad AL-Ishaq (2013)
Synthesis of polysaccharide intercellular adhesin (PIA), accumulation associated protein (Aap) and extracellular matrix binding protein (Embp) are major mechanisms used by Staphylococcus epidermidisto evade immunity through biofilm formation. These evasion strategies are particularly suited for colonisation of medical devices such as heart valves, joint prostheses and central venous catheters resulting in significant patient morbidity. Two biological activities of PIA, Aap and Embp contribute to their role as an evasion molecules. Firstly their ‘barrier’ function limiting penetration of immune cells and antibiotics. Secondly, their ‘immunomodulatory’ properties which influence cytokine responses. At present little is known about these functional activities in physiological media and biological fluids.This thesis uses a cell biology approach to study the environment necessary for PLA production. Specifically in vitromodelling of biofilm formation, PIA production and S. epidermidisleukocyte co-culture experiments have been used to assess conditions that are conducive for PIA production.This thesis has identified that:• Specific cell culture media cause unique profiles of biofilm accumulation with differential production of PIA, Aap and Embp.• Fetal bovine serum and pooled human serum support S. epidermidisgrowth but differentially affect biofilm formation by PIA, Aap and Embp.• Large scale production of PIA (~20mg) can be achieved by culturing in Iscove's Modified Dulbecco's Media which has allowed streamlining of current isolation procedures.• PIA induction of cytokines, including IL-8 and TNF is dependent on being tethered to the bacterial membrane.• Macrophages can penetrate into a S. epidermidisproduced PIA ‘barrier’.• Immunosuppression of whole blood with dexamethasone unmasks the pathogenic advantage of PIA in S. epidermidisexpressing PIA compared to negative controls.• Whole blood killing of S. epidermidisis dependent on CD1 lb/CD 18.• PIA induces whole blood killing dysfunction which is likely related to C5a production.• PIA can be produced in a whole blood environment.• Inocula of -1 0 colony forming unit of S. epidermidisare required to form biofilms in whole blood.This study suggests the importance of studying clinically important biofilm production mechanisms under conditions that closely resemble those in human disease.